Data dissemination of VANET based on lower bound of road delay - Xin PENG; Ren-fa LI; Zhe-tao LI; Guo-qi XIE (Tongxin xuebao)
A reliable VANET data dissemination method was proposed.The method used the traffic information to estimate data transmission delay in each road.Compressive sensing method was used to deduce the lower bound of data transmission delay among each intersection.These information could assist carrier to choose forward routing.In the process of data forward,the vehicle that its route more similar with the forwarding data will be chosen as the next carrier.Furthermore,data forward probability at intersection was deduced based on Markov model.The simulation results demonstrate that presented method achieves lower-delay and higher reliable performance than existed packet forward protocols.